Avaliação das alterações hematológicas periféricas em pacientes com Leishmaniose visceral - Prazeres, Jean Lima (2008)
According to World Health Organization (WHO) data there are some 12 million people worldwide with leishmaniasis. In Brazil the etiological agent of visceral leishmaniasis (VL) is Leishmania chagasi, and is the main means of transmission from the parasite to human beings and other hosts mammals is through the biting of the female mosquito of the order diptera insects belonging to the Psychodidae family, whose main vector is the Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva). The visceral leishmaniasis or kala azar is a tropical disease that is characterized by the presence of fever, anemia, hepatosplenomegaly, hemorrhagic manifestations, and linfoadenomegaly, weight loss, tachycardia, dry cough, diarrhea, fever, pancytopenia and hypergammaglobulinemia. The hematological involvement is common in patients with VL, with anemia the most frequent abnormality due to its multifactor nature and prevalence varies depending on the population being studied. It is meant to evaluate the pattern of peripheral alterations of patients with hematological Visceral Leishmaniasis. Blood samples were collected after the diagnosis of researches seeking ways of amastigotes Leishmania sp in bone marrow aspirate in patients (n = 30), Hospital of Infectious Diseases São José, in Fortaleza, in the state of Ceará, in the period from January 2007 to July 2008 and a control group (n = 30) consists of blood donors from HEMOCE. Laboratory tests were performed at the Clinical Analysis Laboratory of the General Hospital of Fortaleza and the Louis Pasteur Medical Diagnosis Laboratory. The counting of blood elements were measured with an ABX blood Pentre 60 gauge, followed by cytomorphology assessment. The biochemical measurements were made in a HITACHI biochemical analyzer Module P800 and Roche ® Modular I. The comparison between the groups, for the average of quantitative variables was performed by Student t-test, for the normal distribution and Mann – Whitney hypothesis data, in case of non-normality of the data. We have statistically considered meaningful values of 0.05. The analysis (n = 30) patients, the study showed that 63% (19) of the patients are from within the State of Ceará and 37% (11)of the patients are from the capital of the state of Ceará, Fortaleza. That 80% (24) of patients are male and 20 (8%) were females. Most of the patients, 57% were aged between 31 to 45 years old. In what concerns the period of time of the disease until the date of laboratory diagnosis, 47% (14) of the patients already had signs of clinical disease with 30 to 90 days. We have to count the male of red blood cells, an average of 3.69 ± 0.6644 (x106/mm3), hemoglobin of 9383 ± 1.3002 (g/dL), Hematocrit of 28.6708 ± 4.0687 (%) for the female count of red blood cells, an average of 3525 ± 0.6233 (x106/mm3), hemoglobin from 8.5666 ± 1.6561 (g/dL), Hematocrit of 26.9666 ± 3.9026 (%) . With regard to RBC indices observed for both sex, cell volume Medium (MCV) of 78.1 ± 7.0 (fL), mean corpuscular hemoglobin (MCH) of 25.42 ± 2.51 (pg), mean corpuscular hemoglobin concentration (MCHC) of 32 ± 2.15 (%), distribution of amplitude of red blood cells (RDW) of 15,337 ± 2435 (%), reticulocyte count of 20.636.63 ± 20.300.39 (/ mm3). Of the morphological analysis showed up a laboratory profile characteristic of the type of anemia and microcytic normocytic and hypochromic followed by normochromic and 65% of the samples found the presence of "rouleax". For the determinations of serum iron had a average of 32.53 ± 17.31 (µg/dL), Transferrin of 146.83 ± 42.19 (mg/dL), Ferritin of 1.339.47 ± 599.05 (ng /ml), Vitamin B12 from 573.5 ± 253.94 (pg/mL), Folic Acid, 10 ± 3.47 (ng/mL). For the average counts of leukocytes observed was 2802.33 ± 2322.16 (n°/mm3), of neutrophils 1426.33 ± 1348.88 (n°/mm3), lymphocytes from 982.60 ± 576.47 (n°/ mm3); monocytes of 350.13 ± 283.47 (n°/mm3), platelet count 120.233.33 ± 90640.89 (n °/mm3). For the determinations of the VHS diagnosis, the patients had an average of 81.77 mm in the first hours of observation. The determination of TAP showed us that the diagnosis of the patients showed an average of 67.87% of activity prothrombin. The analysis it was observed that there is an impairment in VL hematopoese in translating in peripheral blood by a pancytopenia mainly in favor of the erythroid lineage, and the anemia in patients with chronic nature probably